2019
DOI: 10.2147/ccid.s212781
|View full text |Cite
|
Sign up to set email alerts
|

<p>Risk and severity of psoriasis vulgaris in relation to angiotensin II type 1 receptor gene polymorphism and metabolic syndrome</p>

Abstract: BackgroundPsoriasis vulgaris is a chronic inflammatory and proliferative skin disease, characterized by the formation of itchy, erythematous skin patches or plaques. Patients with psoriasis are at an increased risk of developing metabolic syndrome, including obesity, hypertension, diabetes, and atherosclerosis. Recently, angiotensin II (Ang II) has been reported to be associated with the development of psoriasis. Ang II not only increases the blood pressure but is also a potent proinflammatory modulator and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…This finding is in agreement with the result of Banerjee et al (15) , El-Ghareeb et al (16) , but it is in disagreement with the results obtained by Toker et al (17) and Ahmed (18) as they found that, total cholesterol level didn't show significant difference between the patients. It has been suggested that psoriasis, like atherosclerosis, is an autoimmune disease.…”
Section: Discussionsupporting
confidence: 67%
“…This finding is in agreement with the result of Banerjee et al (15) , El-Ghareeb et al (16) , but it is in disagreement with the results obtained by Toker et al (17) and Ahmed (18) as they found that, total cholesterol level didn't show significant difference between the patients. It has been suggested that psoriasis, like atherosclerosis, is an autoimmune disease.…”
Section: Discussionsupporting
confidence: 67%
“…Our search strategy ( Figure 1 and Methods section) identified 36 studies that met our inclusion criteria ( Bayoumi et al, 2007 ; Bayoumy et al, 2012 ; Boumaiza et al, 2012a ; Boumaiza et al, 2012b ; Ghattas et al, 2013 ; Mohamed Youssef et al, 2013 ; Zadjali et al, 2013 ; Ajjemami et al, 2014 ; Al-Daghri et al, 2014 ; Mackawy and Badawi, 2014 ; Youssef et al, 2014 ; Ajjemami et al, 2015 ; Mehanna et al, 2015 ; Alnory et al, 2016 ; Mehanna et al, 2016 ; Elouej et al, 2016a ; RaafatAbdRaboh et al, 2016 ; Elouej et al, 2016b ; Elouej et al, 2016c ; Khella et al, 2017 ; Hasan et al, 2017 ; Lakbakbi El Yaagoubi et al, 2017 ; Mackawy, 2017 ; Morjane et al, 2017 ; Ismail et al, 2019 ; Ibrahim and Bastawy, 2020 ; Salami and El Shamieh, 2019 ; ElGhareeb et al, 2019 ; Nizam et al, 2019 ; Boulenouar et al, 2019 ; Aljaibeji et al, 2020 ; Osman et al, 2020 ; Alenad et al, 2020 ; Hechmi et al, 2020 ; Kefi, 2021 ). In most cases, studies were excluded because they lacked detailed results, such as odds ratios, confidence intervals, and p -values.…”
Section: Resultsmentioning
confidence: 99%
“…Malondialdehyde (MDA) and nitric oxide (NO) are indicators of oxidative metabolism. MDA is the end product of lipid oxidation, and its content increases in the serum of psoriasis patients [37][38][39]. NO can be highly expressed in keratinocytes and endothelial cells under the stimulation of immune factors.…”
Section: Discussionmentioning
confidence: 99%